2020
DOI: 10.35913/jk.v8i1.196
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Pemanfaatan Posbindu Kesehatan Wanita Usia Subur

Abstract: Background: Women's health is an example of public health. A container that can be used by women of childbearing age in detecting, understanding, obtaining and applying health measures, one of which is an integrated posted cooperation or Posbindu. Many posbindu members who have not been attended routinely in Posbindu activities because of several factors that affect. According to health staff assitent, stated that if knowledge, posbindu activities, attitudes, mileage, and family support are things that affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…The level of knowledge about contraception was an influential factor in the choice of contraception for mothers in the working area of the Mengwi II Health Center (p=0.010). Similar results to previous studies found a significant effect of knowledge on the choice of contraceptives in women of childbearing age (Fatmawati, 2017). Lack of access to information related to contraception becomes a problem, especially for adolescents from low and middleincome countries.…”
Section: Discussionsupporting
confidence: 89%
“…The level of knowledge about contraception was an influential factor in the choice of contraception for mothers in the working area of the Mengwi II Health Center (p=0.010). Similar results to previous studies found a significant effect of knowledge on the choice of contraceptives in women of childbearing age (Fatmawati, 2017). Lack of access to information related to contraception becomes a problem, especially for adolescents from low and middleincome countries.…”
Section: Discussionsupporting
confidence: 89%
“…Sebaliknya, jika kedua tempat itu sangat berjauhan, aksesibilitas antara keduanya rendah. Hasil penelitian Wirata, R.B dan Daning W.I tahun 2020 yang dilakukan di Yogyakarta menemukan jika faktor jarak tempuh memiliki hubungan terhadap pemanfaatan posbindu dengan nilai p-value 0.000 (11).…”
Section: Hubungan Jarak Dengan Utilitas Posbindu Ptmunclassified
“…keluarganya mendukung. Penelitian ini tidak sejalan dengan penelitianWirata and Istianti, (2020) yang menyatakan dukungan keluarga tidak berkorelasi dengan pemanfaatan posbindu kesehatan WUS dengan hasil uji statistik menunjukkan p-value 0,679 atau lebih dari α (0.05). Ketika saya tanya kepada masyarakat "apakah ibu mengetahui apa itu posbindu" respoonden menjawab "saya tidak tahu, saya ikut cek kayak gini baru kali ini" kemudian saya bertanya "darimanakah ibu tau ada pengecekan kesehatan disini bu?"…”
unclassified